Bibliometric Analysis of Trends Project Based Learning (PjBL) Integrated STEM For Twenty First Century Skills Enhancement in Physics Learning - Fauziah Ulmi; Asrizal (Universitas Negeri Padang, 2024)
Twenty first century skills are very important skills in learning because these skills are able to prepare individuals to face challenges and opportunities in the future masses. This study aims to analyze the trend of project-based learning (PjBL) integrated in Science, Technology, Engineering, and Mathematics (STEM) to improve twenty first century skills in Physics learning. The method used is bibliometric analysis method. A total of 127 articles were collected through the Publish or Perish (PoP) application based on relevant keywords in Google Scholar indexed journals. The article was processed using the VOSviewer application. VOSviewer mapping results were analyzed and described. The results of this study are that in the last five years (2020 - 2024), STEM-integrated PjBL has become one of the trends in Physics learning in schools. This can be seen from the many articles found about STEM-integrated PjBL. However, research related to STEM-integrated PjBL to improve twenty first century skills in Physics learning still needs to be done.Twenty first century skills are very important skills in learning because these skills are able to prepare individuals to face challenges and opportunities in the future masses. This study aims to analyze the trend of project-based learning (PjBL) integrated in Science, Technology, Engineering, and Mathematics (STEM) to improve twenty first century skills in Physics learning. The method used is bibliometric analysis method. A total of 127 articles were collected through the Publish or Perish (PoP) application based on relevant keywords in Google Scholar indexed journals. The article was processed using the VOSviewer application. VOSviewer mapping results were analyzed and described. The results of this study are that in the last five years (2020 - 2024), STEM-integrated PjBL has become one of the trends in Physics learning in schools. This can be seen from the many articles found about STEM-integrated PjBL. However, research related to STEM-integrated PjBL to improve twenty first century skills in Physics learning still needs to be done.